1966
DOI: 10.1111/j.1467-6494.1966.tb01717.x
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement value: a suggested idiographic, intensity dimension of meaningfulness for the personality theorist

Abstract: There are two generally conceded aspects to the meanmg of language the denotative and the coimotative meanmgs it bears. Meanmg refers to the intent or the aim of an item of communication, vi^hether that item be a wntten or spoken word, statement, or possibly even some nonverbal sign or token like a raised eyebrow Meanmg is therefore tied to the very mtention of a language system, as an act of expression, including the biased vantage of a pomt of view When the mtent is marked out plainly and clearly, so that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

1973
1973
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 13 publications
(4 reference statements)
0
27
0
Order By: Relevance
“…Edwards (1969) found that individuals are less likely to remember negative than positive descriptions of themselves. Positive words are also learned faster than negative words (Bunch & Wientge, 1933;Rychlak, 1966), and people judge positive phenomena more accurately than negative phenomena. Managers, for example, are much more accurate in rating subordinates' competencies and proficiencies when they perform correctly than when they perform incorrectly (Gordon, 1970).…”
Section: Natural Tendencies Toward the Positivementioning
confidence: 99%
“…Edwards (1969) found that individuals are less likely to remember negative than positive descriptions of themselves. Positive words are also learned faster than negative words (Bunch & Wientge, 1933;Rychlak, 1966), and people judge positive phenomena more accurately than negative phenomena. Managers, for example, are much more accurate in rating subordinates' competencies and proficiencies when they perform correctly than when they perform incorrectly (Gordon, 1970).…”
Section: Natural Tendencies Toward the Positivementioning
confidence: 99%
“…Accordingly, the subjects could rate each item as to the following categories: (a) the trigram has word-quality and I like it (AV-yes, RV-positive) ; (b) the trigrani has word-quality and I dislike it (AV-yes, RV-negative) ; (c) the trigram has no word-quality and I like i t (AV-no, RV-positive) ; or (d) the trigram has no word-quality and I dislike it (AV-no, RV-negative). Following the usual procedure for establishing rating reliability in reinforcement value research (see Rychlak, 1966), the rating scales were administered to the subjects on a second occasion with 48 hours intervening. Those items rated identically on both administrations were regarded as reliably rated.…”
Section: Methodsmentioning
confidence: 99%
“…The meaning "put on" by positive evaluations is said to facilitate the learning of liked materials. I n support of the theory, it has been established experimentally that liked materials are learned more rapidly than disliked materials (see Rychlak, 1966; Rychlak, Tasto, & Andrews, 1973; Rychlak, Tuan, & Schneider, 1974. ) While it is contended that this psychological phenomenon is universal, recent research has revealed that personality and sociocultural factors tend to influence affective learning style.…”
mentioning
confidence: 91%
“…The RV phenomenon has been found m pairedassociate learmng and in free recall studies, usmg either mixed or unmixed lists Leammg effects have also been found m the recognition of designs, abstract paintmgs, and pictures of human faces which have been prerated for RV The age range of subjects m which RV effects on leammg have been noted spans first grade through past 50 years But RV was specifically designed for personality research, and it IS here that some of the most suggestive findmgs have emerged Thus, it has been found that whereas most normal subjects do mdeed learn their hked materials more readily than their dishked matenals, abnormal subjects (schizophremcs) either collapse this RV-positive effect to insignificance or reverse it entirely (l e , actually learn their disliked matenals more rapidly than their hked) The underachieving high school subject IS found to rely more on RV differences m memorizmg verbal materials than the overachiever, who somehow reduces but does not eliminate such evaluative aspects of learnmg altogether (Rychlak & Tobm, 1971) Tachistoscopic recogmtion of faces is seen to be f acihtated by positive RV m certain cases and mhibited by negative RV m others (Rychlak, Galster, & McFarland, 1972) FmaUy, m what is probably the most mterestmg finding to date, black females have been shown to learn more along RV than AV relative to white females, who show the opposite predilection (Rychlak, Hewitt, & Hewitt, m press) There remams an apphcation of the RV dimension which has been lmphed but never actually tested (see Rychlak, 1966) That IS, as a metric the RV dimension should be useful m arraying subjects m a leammg task havmg meaningful relevance to what we know of them as personalities For example, what if mascuhne subjects were asked to leam both masculme and femmine materials? Would there be a direct tie of personahty to learmng style, so that masculme subjects would find mascuhne materials the easiest to acquire?…”
mentioning
confidence: 95%
“…In addition to AV estimates of meanmgfulness, the concept of reinforcement value (RV) has been advanced as a theory of meanmgfulness, one which is presumed to function independent of sheer frequency (see Rychlak, 1966, for the Initial speculations) The RV construct has usually been assessed ldiographically, although it is entirely feasible that nomothetic tables of CVC tngrams or words might be arrayed for specified populations, on the order of Silverstem and Dienstbier (1968). The RV construct is operationally measured by havmg the subject ldiographicaUy prerate his leamable materials according to a fourstep ratmg of "like much (LM), like shghtly (LS), dishke shghtly (DS), and dislike much (DM) " A umque feature of the RV testmg procedure is that the subject always rates his leamable materials on two occasions, smce it was found that unrehable or "ambivalent" judgments of hkabihty did emerge and could be removed from lists with considerable improvement m predictabihty…”
mentioning
confidence: 99%